Desmoplastic fibroma of the rib with cystic change. Issue 2 (February 2016) - Kalimuthu, Sangeetha N.; Chetty, Runjan
Abstract: Desmoplastic fibroma (DF) is a rare, locally aggressive bone tumour, first described by Jaffe in 1958. DF earned its appellation as a result of its morphological resemblance to desmoid-type fibromatosis. The majority of DFs occur in the long bones, mandible and ilium. Presentation in the rib is extremely rare with only six cases reported previously. We report a case of a 42-year-old woman with DF of the rib. Microscopically the tumour was paucicellular comprising bland slender stellate to spindle cells, embedded in abundant loose myxocollagenous stroma. In addition, focal cystic change was noted. There was no specific immunohistochemical staining and importantly B-catenin stain showed a predominantly cytoplasmic staining. DF is associated with an indolent clinical course if adequately excised. As these tumours share morphological similarities with other fibrous/fibro-osseous tumours of bone and soft tissue, awareness is crucial to avoid misdiagnoses.